Price Adjustment in Costa Rica: A First Assessment Using Micro-Data - Vindas Quesada, Alberto José (2014)
This article explores the pricing adjustment process in Costa Rica, taking a deeper look into the micro-data that make up the Consumer Price Index for the period 2006-2013. The basic question asks if this process resembles time-dependent picing models, or if it resembles more a state-dependent process. This is done analysing a series of random effects regressions to explore the relations between inflation rate, frequency of pricing adjustments and their average magnitude. The main conclusions are that 1) there is considerable heterogeneity between product categories, 2) price decreases follow a very stable pattern that does not depend on the overall inflation rate, 3) the average size of the price increases is influenced by a very small magnitude by the inflation rate, 4) the proportion of prices increasing each month is strongly positively correlated with the inflation rate, and 5) state-dependent specifications fit better these facts.